2019
DOI: 10.1038/s41598-019-39434-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Akt-mTOR pathway rescued the social behavior in Cntnap2-deficient mice

Abstract: Autism spectrum disorders (ASD) form a heterogeneous, neurodevelopmental syndrome characterized by deficits in social interactions and repetitive behavior/restricted interests. Dysregulation of mTOR signaling has been implicated in the pathogenesis of certain types of ASD, and inhibition of mTOR by rapamycin has been demonstrated to be an effective therapeutics for impaired social interaction in Tsc1 +/ − , Tsc2+/ − , Pten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 44 publications
3
45
2
Order By: Relevance
“…The adverse changes in brain metabolism in offspring from obese dams include altered mammalian target of rapamycin (mTOR) signalling in the rat hypothalamus [ 79 ] and in the mouse hippocampus [ 97 ]. Dysregulation of mTOR signalling has been implicated in memory formation [ 104 , 105 ], developmental disorders such as autism spectrum disorder [ 106 , 107 ] and mood disorders [ 108 ]. mTOR signalling and proinflammatory mediators such as IL1β and TNFα have a reciprocal relationship and together maintain innate immune homeostasis [ 109 , 110 ].…”
Section: Underlying Mechanisms By Which Maternal Obesity Programs mentioning
confidence: 99%
“…The adverse changes in brain metabolism in offspring from obese dams include altered mammalian target of rapamycin (mTOR) signalling in the rat hypothalamus [ 79 ] and in the mouse hippocampus [ 97 ]. Dysregulation of mTOR signalling has been implicated in memory formation [ 104 , 105 ], developmental disorders such as autism spectrum disorder [ 106 , 107 ] and mood disorders [ 108 ]. mTOR signalling and proinflammatory mediators such as IL1β and TNFα have a reciprocal relationship and together maintain innate immune homeostasis [ 109 , 110 ].…”
Section: Underlying Mechanisms By Which Maternal Obesity Programs mentioning
confidence: 99%
“…In the TRIM32 -/model, the authors generated impaired GABAergic interneurons and leading autism relevant behaviors in mice, concomitant with an increased autophagy mechanism. Therefore, they suggested that theTRIM32 -/mouse is a novel autism mouse model [84] .…”
Section: Mtor Related Modelsmentioning
confidence: 99%
“…Abnormal phenotypes in mouse models relevant to ASD have reportedly been improved by statins 9 , Akt/mTOR inhibitors 10 , mGlu5 receptor negative allosteric modulators 11 , mGlu5 receptor positive allosteric modulators 12 , 13 , and GABA-B receptor agonists 14 16 . However, these findings have not translated successfully to clinical trials 17 19 ; see also 20 .…”
Section: Introductionmentioning
confidence: 99%